ACUTE SUICIDAL POISONING BY ALUMINUM PHOSPHIDE: RARE CASE REPORT FROM NORTHERN RURAL INDIA - KOHLI, KANIKA; SINGH, RANJODH JEET; KOCHHAR, SONIA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Aluminum phosphide (ALP) is a highly toxic pesticide and is lethal if abused as a suicidal agent invariably. The ALP or a celphos powder is a major contributor to mortality, as such celphos poisoning lacks a specific antidote. The management of the patients includes fast decontamination and all international protocol supportive measures. The ALP poisoning has gained enormous interest with the spike in the number of cases due to its increased use for non-agricultural purposes as well. The easy ease of availability and laxity in the implementation of the sale of pesticides has eventually led to misuse, rather an abuse for the commitment of suicide. Celphos powder is commonly available in the form of tablets. This is a case of suicidal consumption of ALP by 54 years old male, a farmer by occupation. According to our interpretation, we believe that strict implementation of pesticide laws must be enforced and suicide help awareness programs under the banner of government and non-government organizations must come in the front line up.